Structure and fracture characterization of the Jizan group: Implications for subsurface CO2 basalt mineralization - Fedorik, Jakub; Delaunay, Antoine; Losi, Giacomo; Panara, Yuri; Menegoni, Niccolo; Afifi, Abdulkader M.; Arkadakskiy, Serguey; Al Malallah, Murtadha; Oelkers, Eric; Gislason, Sigurður R.; Ahmed, Zeyad; Kunnummal, Noushad (Frontiers in Earth Science, 2023)
The coastal region of southwest Saudi Arabia contains a thick sequence of Late Oligocene basalts in the Jizan Group, which accumulated along the continental rift that preceded the opening of the Red Sea. These basalts are targeted for the disposal of CO2 emitted from industrial sources by subsurface carbon mineralization processes. The disposal potential of the Jizan Group basalts depends on having adequate permeability along fracture networks capable of conducting injected fluids away from the wellbores. The basalts in the Jizan Group generally lack primary permeability due to hydrothermal alteration, but are cross-cut by a dense network of fractures. In this paper, we describe and interpret the structural geology of the area based on field and geophysical data, and characterize the fracture development in the Jizan Group. The Jizan Group in the area comprises a bimodal suite of 30-21 Ma volcanic and volcaniclastic rocks and lacustrine sediments that accumulated in a continental rift valley similar to the East African rift. It consists predominantly of basaltic lavas that were fed by dense swarms of sheeted basalt dikes intruded parallel to the rift axis. Structurally the area is composed of half grabens bounded from the west by antithetic normal faults, and from the east by a megaflexure. Fractures in the Jizan Group were characterized by ground and aerial digital photogrammetry of outcrops. Mean P21 fracture intensities from 12 scattered meter scale outcrops are in the range 5-54 m-1, which demonstrates that the Jizan Group is highly fractured. Fracture directions are multimodal. The dominant fracture trend is 140-160N, which is parallel to the sheeted dike swarms and normal faults, and therefore parallel to the paleo-rift axis. Additional conjugate and orthogonal fracture sets are also recognized. The presence of pervasive fracture-based permeability in the Jizan Group will facilitate the injection and mineral carbonation of carbon dioxide in the mafic volcanic rocks in this region.